Estetika Keseimbangan dalam Wayang Kulit Purwa: Kajian Strukturalisme Budaya Jawa - Subiyantoro, Slamet (Gelar: Jurnal Seni Budaya, 2021)
The purpose of this study was to examine the aesthetic value of balance in Wayang Kulit Purwa from the perspective of Javanese cultural structuralism. This type of research is descriptive qualitative with data sources from informants, places/events, and documents/archives. The object of this research is Wayang Purwa with the profile of knight, giant, goddess, and civil servant who were selected by purposive sampling technique. Data were collected by using in-depth interviews, participatory observation, and document analysis. Data were analyzed using interactive techniques with data reduction procedures, data display and data verification. The result of the research shows that the Wayang Kulit Purwa is a picture of real human life. The puppet characters have their own characters which generally consist of good, evil, gentle, and simple characters. Humans created by God are not the same but with a variety of characters. The characters, characteristics, and other structures tend to be opposite, however, there is no attempt to negate each other, instead they complete each other.